A cohort evaluation on arterial stiffness and hypertensive disorders in pregnancy - Lim Wai Yee; Saw Seang Mei; Tan Kok Hian; Yeo George SH; Kwek Kenneth YC (BMC, 2012)
Abstract Background Hypertensive disorders in pregnancy are associated with systemic endothelial dysfunction leading to impaired physiological vasodilation. Recent evidence has shown central aortic pressures obtained through pulse wave analysis, at less than 14 weeks of gestation, to be predictive of pre-eclampsia. In light of this, we aimed to evaluate the role of central aortic stiffness in the prediction and discrimination of hypertensive disorders in pregnancy. Methods A cohort study of women with viable, singleton pregnancies at less than 14 weeks of amenorrhoea, and without multiple pregnancies, autoimmune or renal disease, diagnosed with aneuploidy or fetal anomaly will be recruited from a single maternity hospital and followed up till delivery and puerperium. A targeted sample size of 1000 eligible pregnant women will be enrolled into the study from antenatal clinics. Main exposure under study is central aortic pulse pressure using radial pulse wave recording, and the outcomes under follow-up are gestational hypertension and pre-eclampsia. Other measures include lifestyle factors such as smoking, physical exercise, psychometric evaluations, vasoactive factors, uterine artery pulsatility index, height and weight measurements. These measures will be repeated over 4 antenatal visits at 11-14, 18-22, 28-32 and above 34 weeks of gestation. Double data entry will be performed on Microsoft Access, and analysis of data will include the use of random effect models and receiver operating characteristic curves on Stata 11.2. Discussion The proposed study design will enable a longitudinal evaluation of the central aortic pressure changes as a marker for vascular compliance during pregnancy. As measures are repeated over time, the timing and severity of changes are detectable, and findings may yield important information on how aberrant vascular responses occur and its role in the early detection and prediction of hypertensive disorders.